Norfloxacin inhibited the growth, development and reproduction of Grapholita molesta by reducing the abundance of Enterobacteriaceae bacteria in the guts of larva and ovaries of female moth - Shaokai Liu; Xueying Liu; Donghan Wang; Junjie Li; Yanshen Fu; Chunyang Guo; Huilin Tang; Junheng Gao; Xiangqun Yuan; Yiping Li (Ecotoxicology and Environmental Safety)
While antibiotics are occasionally used in orchard bacterial disease management, their ecological impacts remain understudied. This investigation reveals significant sublethal effects of norfloxacin on the key fruit tree pest Grapholita molesta (oriental fruit moth). Our results showed that the antibiotic norfloxacin induced multiple developmental alterations by reducing the abundance of Enterobacteriaceae bacteria in the larval guts and adult ovaries: larval stage prolongation (+8.64 %), reduced pupal weight (-6.95 %), shortened adult period (-9.55 %), and impaired female fecundity with 24.77 % lower egg production and 16.57 % reduced egg hatchability. Our findings demonstrate that optimized antibiotic applications could simultaneously manage bacterial pathogens and suppress pest populations, providing dual agricultural benefits. This study proposes a novel integrated approach for orchard management through targeted antibiotic utilization.